2022
DOI: 10.1186/s13014-022-02139-7
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63α transcriptionally represses p53 target genes involved in the radiation-induced DNA damage response

Abstract: Background The DNA damage response (DDR) is a mechanism that protects cells against radiation-induced oxidative DNA damage by causing cell cycle arrest and apoptosis. TP63 is a member of the tumour suppressor TP53 gene family, and ΔNp63α, a TP63 splicing variant, is constitutively expressed in the stem cell-containing basal layer of stratified epithelial tissues, including the mammary gland, where it plays a critical role in stemness and tissue development. ΔNp63α has been reported to transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Kudo et al recently showed that ΔNp63 knockdown increases radiation-induced apoptosis in normal mammary epithelial cells expressing ΔNp63 [ 22 ]. In addition, they reported that ΔNp63α represses the p53-related radiation-induced DNA damage response, thereby inducing radioresistance of mammary epithelial stem cells [ 22 ]. Here, we found that ΔNp63 knockdown enhanced radiation-induced apoptosis in HNSCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kudo et al recently showed that ΔNp63 knockdown increases radiation-induced apoptosis in normal mammary epithelial cells expressing ΔNp63 [ 22 ]. In addition, they reported that ΔNp63α represses the p53-related radiation-induced DNA damage response, thereby inducing radioresistance of mammary epithelial stem cells [ 22 ]. Here, we found that ΔNp63 knockdown enhanced radiation-induced apoptosis in HNSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bretz et al reported that ΔNp63 activates the Fanconi anemia DNA repair pathway and limits the efficacy of DNA-damaging agent cisplatin treatment in SCC [ 21 ]. Recently, Kudo et al also reported that ΔNp63α represses the p53-related DNA damage response after irradiation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…TAp63 protein is instead expressed in luminal cells [ 78 ]. The expression of ΔNp63 in mammary progenitor cells serves to maintain their undifferentiated state and quiescence and therefore to promote stem cell activity [ 31 , 74 , 79 81 ]. In addition, it has been reported that ΔNp63 can reprogram adult luminal into basal cells by promoting an intermediate multipotent-like state, thus supporting the concept of reversible plasticity in epithelial cell fate [ 71 , 82 ].…”
Section: Role Of P63 In Epithelial Stem Cell Biologymentioning
confidence: 99%